Hepatitis C Virus Treatment Access Among Human Immunodeficiency Virus and Hepatitis C Virus (HCV)-Coinfected People Who Inject Drugs in Guangzhou, China: Implications for HCV Treatment Expansion. (24th June 2016) - Chu, Carissa E.; Wu, Feng; He, Xi; Zhou, Kali; Cheng, Yu; Cai, Weiping; Geng, Elvin; Volberding, Paul; Tucker, Joseph D.
Abstract: Background. Hepatitis C virus (HCV) treatment access among human immunodeficiency virus (HIV)/HCV-coinfected people who inject drugs is poor, despite a high burden of disease in this population. Understanding barriers and facilitators to HCV treatment uptake is critical to the implementation of new direct-acting antivirals. Methods. We conducted in-depth interviews with patients, physicians, and social workers at an HIV treatment facility and methadone maintenance treatment centers in Guangzhou, China to identify barriers and facilitators to HCV treatment. We included patients who were in various stages of HCV treatment and those who were not treated. We used standard qualitative methods and organized data into themes. Results. Interview data from 29 patients, 8 physicians, and 3 social workers were analyzed. Facilitators and barriers were organized according to a modified Consolidated Framework for Implementation Research schematic. Facilitators included patient trust in physicians, hope for a cure, peer networks, and social support. Barriers included ongoing drug use, low HCV disease knowledge, fragmented reimbursement systems, HIV exceptionalism, and stigma. Conclusions. Expanding existing harm reduction programs, HIV treatment programs, and social services may facilitate scale-up of direct-acting antivirals globally. Improving integration of ancillary social and mental health services within existing HIV care systems may facilitate HCV treatment access.